An Atomic Insight into the Chemical Origin and Variation of the Dielectric Constant in Liquid Electrolytes. (20th August 2021) - Yao, Nan; Chen, Xiang; Shen, Xin; Zhang, Rui; Fu, Zhong‐Heng; Ma, Xia‐Xia; Zhang, Xue‐Qiang; Li, Bo‐Quan; Zhang, Qiang
Abstract: The dielectric constant is a crucial physicochemical property of liquids in tuning solute–solvent interactions and solvation microstructures. Herein the dielectric constant variation of liquid electrolytes regarding to temperatures and electrolyte compositions is probed by molecular dynamics simulations. Dielectric constants of solvents reduce as temperatures increase due to accelerated mobility of molecules. For solvent mixtures with different mixing ratios, their dielectric constants either follow a linear superposition rule or satisfy a polynomial function, depending on weak or strong intermolecular interactions. Dielectric constants of electrolytes exhibit a volcano trend with increasing salt concentrations, which can be attributed to dielectric contributions from salts and formation of solvation structures. This work affords an atomic insight into the dielectric constant variation and its chemical origin, which can deepen the fundamental understanding of solution chemistry. Abstract : The dielectric constants of solutions at different temperatures and compositions are comprehensively probed by considering the significant role in regulating solute–solvent interactions and solvation structures of working liquid electrolytes.